From Consumer Experience to Purchase Decision: The Role of Brand Image in Local Coffee Shops - Via Anaza, Sissy; Risnawati Istirahayu, Nanik (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2026)
The rapid growth of local coffee shops has intensified competition in the food and beverage industry, encouraging businesses to shift their focus from product offerings to consumer-centered strategies. This study aims to analyze the influence of consumer experience and brand image on purchase decisions at a local coffee shop, Terror Coffee Roastery, located in West Bandung Regency. The research adopts a quantitative approach using a case study method. Data were collected through a survey of 60 consumers selected via convenience sampling from a population of 150 customers. The analysis employed descriptive statistics and inferential techniques, including validity and reliability tests, classical assumption tests, and simple and multiple linear regression analyses. The results indicate that consumer experience has a significant effect on purchase decisions, explaining 48.4% of the variance (R² = 0.484), while brand image contributes 49.5% (R² = 0.495). Simultaneously, consumer experience and brand image significantly influence purchase decisions with a combined explanatory power of 56.6% (R² = 0.566). These findings demonstrate that positive consumer experiences supported by a strong brand image play a critical role in encouraging purchase decisions in local coffee shops. This study highlights the strategic importance of managing consumer experience and brand image as key drivers of competitiveness and sustainable growth in the local coffee shop industry. Keywords: Consumer Experience; Brand Image; Purchase Decision; Local Coffee Shop